Use of 50% Dextrose as the Distension Medium During Cystoscopy for Visualization of Ureteric Jets. Issue 4 (April 2016) - Narasimhulu, Deepa M.; Prabakar, Cheruba; Tang, Nancy; Bral, Pedram
Abstract : Obstet Gynecol Surv 2016;71(4):219–221 The lower urinary tract is at risk of injury during pelvic surgery.